Bērnu runas specifika izglītības aktualitātes kontekstā. - MARKUS, DACE (SCRIPTUS MANET: Journal of Humanities & Arts, 2019)
The basic task in the studies on children's language acquisition is to establish how successfully or unsuccessfully children have acquired a language according to their age group and development. A group of researchers from Liepāja University in cooperation with Rēzekne Academy of Technologies and the Institute of Mathematics and Computer Science, University of Latvia, are studying language acquisition in the National research programme "Latvian Language". The task is connected with testing children's readiness to learn in the official state language at school. Thus, the study encompasses the testing of the vocabulary, grammar and communication skills in various sociolinguistic situations. The article focuses on some peculiar features of children's language rooted in the Latvian language, and even in the systems of the Baltic languages. As linguists develop tools for testing children's language skills, the identified children's speech peculiarities should be considered (for example, the possibility of ie > ī and o [uo] > ū, the interchange between voiced/voiceless consonants in different positions in a word or a sentence), also causes of peculiarities should be identified in the testing process (considering dialectal influences, and the impact of other languages, or difficulties in articulation). It should be understood that the language system and the norm are not identical because children form their own individual systems as illustrated by the usage of prefixes in verb formation as described in the article. Because children create new words and word forms, they create pairs of antonyms so characteristic for their unique language because every prefix in the Latvian language can express a large variety of meanings. As prefixes change, the meaning of the same corresponding word changes, for example, atlasīt, ielasīt, izlasīt, nelasīt, nolasīt, palasīt, pārlasīt, pielasīt, salasīt, uzlasīt, and even aplasīt. Children have noticed such possibilities and they employ them creatively for one of the most fundamental human functions, namely, to communicate. As children try using the familiar language elements more than they have succeeded in hearing, learning, acquiring from adults' speech, those language elements often result in creations incompatible with those in standard language. Although creative and purposeful, short-term exploitation of language means shows that children have grasped regularity of language units, and thus they are proceeding onto normative usage to be reached in full during the school years.